Evaluasi Implementasi Sistem Perpustakaan Universitas Esa Unggul Kebon Jeruk Dengan Metode Fitgap Dan Risk Analysis - Yosua; Malabay (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
The existing system in the organization will always have changes following the times and newneeds that exist. So that an evaluation is needed, this research aims to find out whether the librarysystem currently implemented is suitable (Fit) or there are still gaps (Gap), which then from theseresults will be used FMEA method based on the existing Gap value, so as to provide suggestionsand evaluation results to achieve the goals of system development. The result of this study is thatthe implemented library system is considered to have a Degree of Fit of 91% (20 userrequirements), Degree of Partial 9% (2 user requirements), Degree of Gap 0% (0 userrequirements). Thus it is concluded that the current library system is still in accordance with userneeds.However, development can be carried out so that the systemcan bemore optimal inmeetinguser needs.